Chinese folk music and its effect on human mathematical thinking skills. (2nd January 2022) - Wang, Qian; Luo, Junyi
ABSTRACT: This work aimed to study the short- and long-term effects of listening to Chinese folk music on mathematical thinking skills. The central research methodology was based on an independent assessment of respondents' success in mathematics with reference to the amount of overall time spent listening to Chinese folk music. The results obtained for the experimental group reported a positive correlation between individuals' mathematical skills and Chinese folk music listening duration, while the control group outcomes turned out to be practically time-independent. The s 2 vale for the Student's t -test, used for the hypothesis testing, for each of the intervals of the mathematical tests ranges from 0.015 to 0.06 for the experimental group and from 0.01 to 0.19 for the control group. An alternative hypothesis about a direct correlation between passive listening to Chinese traditional music and mathematical thinking skills was confirmed using the independent two-sample Student's t -test.